Teacher Strategies for Implementing Communicative Language Teaching in Second-Grade EFL Classrooms in a Pesantren-based Educational Setting - Vatha Nabilla, Noor; Ruminda; Juhana (Linguistic, English Education and Art (LEEA) Journal, 2025)
This study investigates the implementation of the Communicative Language Teaching (CLT) approach by an English teacher in a second-grade EFL classroom within a pesantren-based educational setting in Indonesia. It aims to find out the teacher's teaching strategies to develop communicative competence, particularly in speaking. Through a qualitative research design, the study employed classroom observations across six meetings and a semi-structured interview with the teacher to explore the instructional strategies used, the challenges faced, and the outcomes achieved through the adoption of CLT. Findings reveal that while both the teacher and students initially faced difficulties adapting to the CLT method due to the teacher’s lack of prior experience and the students’ unfamiliarity with student-centered learning, gradual progress was evident. The teacher employed various communicative activities such as role-play, peer interviews, picture narration, and guessing games, which encouraged students to speak more confidently and spontaneously. The “help a friend” strategy, real-life contextual materials, and reduced correction during speech further fostered a supportive environment for language development. The study demonstrated that CLT could enhance student engagement, confidence, and oral proficiency. It offers valuable insights for educators aiming to shift from traditional instruction to more communicative, learner-centered approaches in culturally embedded environments. Keywords: Communicative Language Teaching, Teaching Method, Teaching Strategy, Speaking Skill